ANALISIS PENYAJIAN LAPORAN KEUANGAN DAERAH PP NOMOR 71 TAHUN 2010 PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (BPKAD) KUTAI KARTANEGARA - Listiani, Mutya - (EKONOMIA, 2019)
The aim of the study was to analyze the items of the Budget  Realization Report, the Reports on Changes in Budget Balance Reports, Balance Sheet posts, Operational Report items, Cash Flow Report items, Equity Change Report items, Notes Notes posts.  Financial Report on BPKAD Kutai Kartanegara based on PP No. 71 of 2010 with the following research problems, the employee lacks or does not understand the accrual-based accounting system, so that almost all of them are left to superiors and there are delays in reporting financial statements.           Presentation of Financial Statements at BPKAD Kutai Kartanegara, the components of its financial statements, each item is incomplete and meets accrual-based govermant accounting standards PP No.71 of 2010. The basic theory used is public sector accounting that focuses on the presentation of regional financial statements, PP No. 71 of 2010.  The research hypothesis is the posts of the Budget Realization Report, Reports on Changes in Budget Balance More, Balance Sheet posts, Operational Report posts, Cash Flow Report items, Equity Change Report items, Posts Notes to the Financial Statements preseted by BPKAD Kutai Kartanegara have not been in accordance with Government Regulation No. 71 of 2010. The Analysis tool used in this study is a comparative method, comparing the BPKAD financial statements of Kutai Kartanegara with PP No. 71 of 2010 using the Dean J. Champion formula in 1990.            The results showed that the first hypothesis was accepted that the presentation of Budget Realization Report posts was not appropriate, the second hypothesis is rejected the presetation of the Change Report Budget Budget posts are more suitable, the third hypothesis is accepted the presentation of Neraca posts is not appropriate, the fourth hypothesis is rejected, the presentation of Operational Report posts is quite appropriate, the fifth hypothesis is accepted the presentation of the items of the Cash Flow Statement is not appropriate, the sixth hypothesis is rejected the presentation of Equity Change Report posts is very appropriate, The seventh hypothesis is rejected by the presentation of the items. Notes the Financial Statements are very appropriate.